2019
DOI: 10.1080/08964289.2019.1594671
|View full text |Cite
|
Sign up to set email alerts
|

Can Participants’ Characteristics Predict Benefit from a Multimodal Burnout Prevention Program? Secondary Analysis of a Randomized Controlled Trial Conducted in Germany

Abstract: Chronic psychological distress appears to be increasing markedly among the working population. A recent randomized controlled trial (RCT) supported the effectiveness of a threeweek outpatient burnout prevention program-comprised of stress management interventions, relaxation, physical exercise and moor baths followed by massage-in reducing perceived stress and emotional exhaustion. However, the effectiveness of treatments in the real-world that were shown to be efficacious in RCTs is related to the appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…13 At the individual physician level, the cost can range from $4,100 to $10,200 per physician. 13 The costs of burnout come from reduced professional work effort, 14 resignation/physician turnover, [15][16][17] worker disability, and decreased efficiency, 15,18,19 with many of these financial losses going unnoticed, particularly for academic centers. 15 Although the specific criteria for burnout vary across studies, among medical oncologists, levels of burnout have been reported to range between 32% and 45%.…”
Section: Introductionmentioning
confidence: 99%
“…13 At the individual physician level, the cost can range from $4,100 to $10,200 per physician. 13 The costs of burnout come from reduced professional work effort, 14 resignation/physician turnover, [15][16][17] worker disability, and decreased efficiency, 15,18,19 with many of these financial losses going unnoticed, particularly for academic centers. 15 Although the specific criteria for burnout vary across studies, among medical oncologists, levels of burnout have been reported to range between 32% and 45%.…”
Section: Introductionmentioning
confidence: 99%
“…The original three dimensional structure is well confirmed (Schaufeli et al, 1996) and was also replicated for the German version (Bu ¨ssing & Glaser, 1998). Vanajan et al (2020) reported sufficient strong internal consistencies of the three dimensions of the MBI-GS-D with Cronbach's alpha = 0.86 (emotional exhaustion), Cronbach's alpha = 0.85 (cynicism) and Cronbach's alpha = 0.84 (personal accomplishments).…”
Section: Maslach Burnout Inventory (Mbi)mentioning
confidence: 99%
“…The one dimensional model as used in the current study showed strong internal consistency of Cronbach's alpha = 0.95 (cf. Vanajan et al, 2020).…”
Section: Perceived Stress Questionnaire (Psq)mentioning
confidence: 99%